THE STUDY ON TOLERABILITY AND EFFICACY OF THE NEW COMPLEX DRUG HELMINTAL TABLETS BASED ON MOXIDECTIN AND PRAZIQUANTEL - M. V. Arisov; E. S. Smirnova; G. B. Arisova; V. A. Stepanov; D. S. Poselov (Российский паразитологический журнал)
Objective of research: the study on tolerability and therapeutic efficacy of the complex drug Helmintal produced on the basis of two ingredients moxidectin and praziquantel.Materials and methods: In our research, we used four drug modifications: for cats and kittens weighting less than4 kg (moxidectin 0.4 mg and praziquantel 10 mg); for cats - more than4 kg (moxidectin 1.6 mg and praziquantel 40 mg); for dogs and puppies - less than10 kg (moxidectin 1 mg and praziquantel 25 mg); for dogs - more than10 kg (moxidectin 5 mg and praziquantel 125 mg.) To study the effect of the drug on the organism, three groups of clinically healthy animals were formed (5 animals per group): dogs 1 - 2 years of age with the body mass 18 -20 kg; puppies 3 - 5 weeks of age weighting 0.8 -1 kg; cats 1 - 2 years of age weighting 3 -5 kg; kittens 6 - 8 weeks of age with the body mass 0.6 -0.8 kg. The drug was given to animals orally once a day in the morning within 7 days in the following doses: the first experimental group - 0.4 mg moxidectin and praziquantel 10 mg per1 kg of body weight (double therapeutic dose); the second group - moxidectin 1.0 mg and praziquantel 25 mg per1 kg of body weight (five-fold therapeutic dose); the third group served as controls - the drug was not used. During the experiment, animals were monitored daily, their general health status, behavior, appetite were observed, weight and body temperature controlled. Before and 15 and 30 days after the beginning of the drug taking, several morphological and biochemical parameters of blood and urine were investigated. The study of the anthelmintic efficacy of the drug was carried out on the basis of veterinary clinics inMoscow andMoscow region. Altogether 205 cats and 209 dogs spontaneously infected were chosen for the experiment. The diagnosis and the drug efficacy were confirmed based on the clinical picture and on Fulleborn's method used for detection of helminth eggs in animal's feces followed by differentiation.Results and discussion: During the study on the drug tolerance it was found that the general status, mass and the body temperature of animals from experimental groups did not significantly differ from controls. Morphological and biochemical parameters of blood and urine in all animals from experimental and control groups did not differ significantly and were within the physiological norm before and after treatment. Thus, the research allows to conclude that the drug applied within 7 days at double and five-fold therapeutic doses has no adverse effect on dogs, puppies, cats and kittens. Most sick animals used in the experiment on the effectiveness of the drug, were emaciated, listless, their fur was ruffled, mucous membranes were pale; they suffered from anal itching, diarrhea and fecal retention. The drug was given after diagnosis; many dogs and cats ate it themselves, and other had no problems with eating pills due to their small size and pleasant taste. When applying the drug and throughout the experiment, no side effects and complications were observed in all animals. 10 and 20 days after giving the drug, its efficacy in the treatment of nematodosis and cestodosis of adult dogs cats as well as kittens and puppies was 100%.